The change of inflammatory markers may predict long-term major adverse cardiovascular events in elderly patients with coronary heart disease: a retrospective cohort study - He, Li; Chen, Sisi; Zhu, Xuan; He, Fang (Frontiers in Medicine, 2025)
BackgroundAt present, the relationship among inflammatory markers [monocytes/HDL-c (MHR), neutrophils/HDL-c (NHR) and lymphocytes/HDL-c (LHR)] and long-term prognosis of coronary heart disease (CHD) is still unclear. Therefore, this study explores the relationship between inflammatory indicators and the risk of long-term major adverse cardiovascular events (MACE) in elderly patients with CHD.MethodsA retrospective analysis was conducted on 208 elderly patients who underwent coronary angiography at Wuhan Fourth Hospital from August 2022 to August 2023. They were divided into the CHD group (N = 116) and control group (N = 92). Patients in the CHD group were followed up for 1 year and divided into the MACE group (N = 36) and the non-MACE group (N = 80) according to whether MACE occurred.ResultsIn elderly patients, logistic regression analysis shows that MHR is an independent risk factor for CHD (OR = 3.050, 95% CI 1.318–1.772). ROC curve analysis found that MHR (AUC = 0.865, 95% CI 0.811–0.919, p < 0.001) is higher than NHR and LHR. In patients with CHD, the spearman analysis show that MHR is positively correlated with Gensini score (R = 0.266, p = 0.004). The logistic regression analysis found that MHR is independent risk factors for MACE (OR = 6.048, 95% CI 1.224–1.941, p = 0.002). ROC analysis showed that the critical value of MHR to predict MACE was 0.651, the sensitivity of 58.3% and specificity of 90.0% could predict MACE, and the AUC was 0.793 (95% CI 0.702–0.884, p < 0.001) is higher than LHR.ConclusionIn elderly patients, MHR is an independent predictor of CHD and long-term MACE and is positively correlated with the severity of coronary artery lesions.